2014
DOI: 10.7314/apjcp.2014.15.22.9835
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Fisetin with Targets of the Nuclear Factor-κB Signal Transduction Pathway Activated by Epstein-Barr Virus Encoded Latent Membrane Protein 1

Abstract: Fisetin is an effective compound extracted from lacquer which has been used in the treatment of various diseases. Preliminary data indicate that it also exerts specific anti-cancer effects. However, the manner in which fisetin regulates cancer growth remains unknown. In this study, we elucidated interference of fisetin with targets of the nuclear factor κB signal transduction pathway activated by Epstein-Barr virus encoding latent membrane protein 1 (LMP1)in nasopharyngeal carcinoma (NPC) cells, Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…A research work conducted by Li et al explored the chemopreventive role of fisetin bioactive compound against nasopharyngeal carcinoma (NPC) cells through the suppression of the survival rate of CNE-latent membrane protein 1 (LMP1) cells and NF-κB activation, preventing the nuclear translocation of NF-κB (p65) and IκBα phosphorylation as well as suppressing the cyclin D1 expressions. Li, Liang, et al (2014) showed that they strengthened the previous results regarding anticancer role of fisetin against nasopharyngeal carcinoma (NPC) cells including CNE1-LMP1 cells. Fisetin treatment suppresses the migration and invasion, inhibits molecular changes linked with epithelial-mesenchymal transition (EMT) induced by LMP1, down-regulates the mesenchymal marker and vimentin protein levels, and up-regulates the E-cadherin protein and epithelial marker.…”
Section: Oralsupporting
confidence: 76%
“…A research work conducted by Li et al explored the chemopreventive role of fisetin bioactive compound against nasopharyngeal carcinoma (NPC) cells through the suppression of the survival rate of CNE-latent membrane protein 1 (LMP1) cells and NF-κB activation, preventing the nuclear translocation of NF-κB (p65) and IκBα phosphorylation as well as suppressing the cyclin D1 expressions. Li, Liang, et al (2014) showed that they strengthened the previous results regarding anticancer role of fisetin against nasopharyngeal carcinoma (NPC) cells including CNE1-LMP1 cells. Fisetin treatment suppresses the migration and invasion, inhibits molecular changes linked with epithelial-mesenchymal transition (EMT) induced by LMP1, down-regulates the mesenchymal marker and vimentin protein levels, and up-regulates the E-cadherin protein and epithelial marker.…”
Section: Oralsupporting
confidence: 76%
“…In accordance, potentiation of apoptosis induced by doxorubicin, and cisplatin was observed [73]. Additional evidence of its inhibitory effect on the NF-κB signal transduction pathway came from a study in nasopharyngeal carcinoma cells where fisetin interfered with targets of NF-κB activated by Epstein-Barr virus encoded LMP1 protein [74]. …”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 79%
“…Half of the ingredients in the RDS prescription are classic toxinclearing TCM with antiviral activity, including Forsythiae Fructus, Lonicerae Japonicae Flos, Schizonepetae Herba, Gleditsiae Spina and Nidus Vespae [11]. Among the seven compounds, luteolin [55][56][57][58] and quercetin [59] from Forsythiae Fructus, and fisetin from Gleditsiae Spina [60] have been studied for their toxinclearing and antiviral activities. Besides, some understudied compounds from Glycyrrhizae Radix et Rhizoma (e.g., licoisoflavone B, glyasperin F, isolicoflavonol and semilicoisoflavone-B) have also shown similar inhibitory effects against 3CL pro , indicating their antiviral potential.…”
Section: Discussionmentioning
confidence: 99%